2012
DOI: 10.1002/bio.2443
|View full text |Cite
|
Sign up to set email alerts
|

A new and simple resonance Rayleigh scattering method for human serum albumin using graphite oxide as probe

Abstract: Graphite oxide (GO) was prepared by the Hummer procedure, and can be dispersed to stable colloid solution by ultrasonic wave. The GO exhibited an absorption peak at 313 nm, and a resonance Rayleigh scattering (RRS) peak at 490 nm. In pH 4.6 HAc-NaAc buffer solution, human serum albumin (HSA) combined with GO probe to form large HSA-GO particles that caused the RRS peak increasing at 490 nm. The increased RRS intensity was linear to HSA concentration in the range 0.50-200 µg/mL. Thus, a new and simple RRS metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Graphene oxide (GO) nanosheets have many excellent physical and chemical properties and have been intensively researched with a view to producing new devices in many fields [32][33][34]. GOs contain epoxide, carboxyl, and hydroxyl groups on their basal planes and edges, the abundance carboxyls coordinate with Ag + to form stable GO-Ag n + complex.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graphene oxide (GO) nanosheets have many excellent physical and chemical properties and have been intensively researched with a view to producing new devices in many fields [32][33][34]. GOs contain epoxide, carboxyl, and hydroxyl groups on their basal planes and edges, the abundance carboxyls coordinate with Ag + to form stable GO-Ag n + complex.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of the AgNR/rGO Sol GO can be prepared easily by Hummer procedure [32,33] and AgNR sol was prepared by simple chemical reduction [34]. Using CTAB surfactant as the template and small naosilver as seeds, the AgNR colloids were prepared commonly by vitamin C chemical reduction [34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 − 29 He et al 27 reported that GO prepared by the Hummers method could catalyze the hydrolysis of soybean isoflavones. In the nanoanalysis, 30 38 Wang et al established a resonance Rayleigh scattering (RRS) method to detect HSA, using GO as a probe. 30 The SERS effect of GO was studied by Hao et al 31 The SERS properties of GO/Au/Ag composites were better than those of pure gold and silver nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In the nanoanalysis, 30 38 Wang et al established a resonance Rayleigh scattering (RRS) method to detect HSA, using GO as a probe. 30 The SERS effect of GO was studied by Hao et al 31 The SERS properties of GO/Au/Ag composites were better than those of pure gold and silver nanoparticles. Banchelli’s research group found that GO–Ag composite nanoparticles were more effective than silver nanomaterials when used as a substrate in SERS analysis.…”
Section: Introductionmentioning
confidence: 99%